Radar volume reflectivity estimation using an array of ground based rainfall drop size detectors - Kasparis, Takis; Lane, John E.; Jones, Linwood W. (My University, 2000)
Rainfall drop size distribution (DSD) measurements made by single disdrometers at isolated ground sites have traditionally been used to estimate the transformation between weather radar reflectivity Z and rainfall rate R. Despite the immense disparity in sampling geometries, the resulting Z-R relation obtained by these single point measurements has historically been important in the study of applied radar meteorology. Simultaneous DSD measurements made at several ground sites within a microscale area may be used to improve the estimate of radar reflectivity in the air volume surrounding the disdrometer array. By applying the equations of motion for non-interacting hydrometeors, a volume estimate of Z is obtained from the array of ground based disdrometers by first calculating a three-dimensional drop size distribution (3D-DSD). The 3D-DSD model assumes that only gravity and terminal velocity due to atmospheric drag within the sampling volume influence hydrometeor dynamics. The sampling volume is characterized by wind velocities, which are input parameters to the 3D-DSD model, composed of vertical (updraft/downdraft) and horizontal (advection) components. Reflectivity data from four consecutive WSR-88D volume scans, acquired during a thunderstorm near Melbourne, FL on June 1, 1997, are compared to data processed using the 3D-DSD model and data from three ground based disdrometers of a microscale array.
Keywords: Meteorology; Speed; Image processing; Radar--Measurement; Radar